Annélides Polychètes abyssaux de la campagne Abyplaine au large de Madère - Amoureux, Louis (Bulletin du Muséum d'Histoire Naturelle, Paris, 1986)
About 2000 Polychaetous worms sampled on twelve abyssal stations off Madeira (between 4200-5200 metres depth) during scientific cruise Abyplaine are here listed. They are divided between 36 families and more than 71 species among them one is new for Science : Buskiella minuta (Flabelligeridae) with 220 specimens. Tables give distribution of worms, species and families on the twelve stations. Some morphological notes come then on each species, especially the description of the new species. A comparison between Tunicata and Polychaeta collected on each station and a bibliography end the paper.
World Polychaeta Database (WPolyDb)